Myasthenia Symptom Burden, Fatigue, and Sleep: Are They Related?. Issue 3 (March 2021) - Yang, Sarah; Miglis, Mitchell G.; Jaradeh, Safwan; Muppidi, Srikanth
Abstract: Objective: Our aim is to explore the relationship between myasthenia gravis (MG)-related symptom burden, sleep quality, and fatigue in a diverse group of self-identified MG patients. Methods: Patients provided relevant myasthenia disease data and completed the MG QOL-15, Epworth sleepiness scale, Pittsburgh Sleep Quality Index, and fatigue severity score (FSS) online. MG activities of daily living scale (MG-ADL) was completed on a follow-up telephone interview. Results: One hundred ninety-six patients completed the online survey and 99 provided MG-ADL data. The mean age was 52 ± 15.34 years, 88 were acetylcholine receptor antibody positive, and 21 were muscle specific kinase positive. The mean MG-ADL was 6.81, indicating a moderate MG disease burden. Forty-seven (24%) reported high Epworth sleepiness scale scores, 152 (77%) reported high Pittsburgh Sleep Quality Index scores, and 162 (82%) reported high FSS scores. Correlation analysis correcting for body mass index and sleep apnea revealed a moderate positive correlation between MGQOL-15, MG-ADL, and FSS. Conclusions: There is a moderate positive correlation between various MG-specific outcome measures and fatigue severity.